Taxas de administração de fundos de investimento no mercado brasileiro: o papel da concorrência da indústria e do sentimento do investidor - Leticia Fernandes Pereira (2022)
At the aim was to analyze the influence of fund industry competition and sentiment on investment fund management fees in Brazil. We analyzed a sample of 1290 stock funds, from the subcategories “Value/Growth”, “Dividends”, “Active Index” and “Free Portfolio”, from December 2009 to December 2019. We used concentration index of Herfindahl-Hirschman as a proxy for fund industry competition; and for investor sentiment, we estimated two proxies, the first being built according to the model proposed by Baker and Wurgler (2006) and adapted by Yoshinaga and Castro Júnior (2012), Xavier and Machado (2017) and Miranda and Machado (2019); and the second one corresponded to the natural logarithm of the Consumer Confidence Index (ICC). The methodology consisted of the elaboration of regression models considering the management fee was as dependent variable and, as explanatory variables, the proxies of competition and investor sentiment, in addition to other control variables. First, we estimated a regression model for panel data in which the administration fee was analyzed at its level; and then we estimated a Logit/Probit regression model in which the administration fee was a dichotomous variable, which referred to the change, or not, of its value in relation to the previous period. As a result, we could not observe statistical significance at 5% level for fund industry competition; and the investor sentiment proxy that used the natural logarithm of the ICC was statistically significant at 5% level to explain the value of management fees (positive relationship) and their probability of change, mainly for setting higher fees.